The Effect of Group Counseling with Game Techniques to Improve Academic Resilience among Vocational Students - Febriana Febriana; Andriani Paulin Nalle; Lolang Maria Masi; I Putu Agus Apriliana (Universitas PGRI Yogyakarta, 2026)
Academic resilience is an essential component in helping vocational students overcome academic setbacks, challenges, difficulties, and pressure. However, many vocational students exhibit low levels of academic resilience, particularly in maritime and technical fields. This study aims to assess the effectiveness of game-based techniques in group counseling for improving academic resilience among vocational high school students. A quantitative method with a pseudo-experimental one-group pretest-posttest design was employed. The sample consisted of 10 vocational students identified with moderate and low academic resilience based on the pre-test using the Academic Resilience Scale (11 valid and reliable items, scoring 1-4). The intervention comprised group counseling sessions integrating cooperative movement cup games across two stages. Data were analyzed using a paired sample t-test. The results showed a significant increase in the mean academic resilience score from 2.81 (pre-test) to 3.05 (post-test). The paired-samples t-test revealed t = -2.390 (p < 0.05), and Cohen's d was 0.96 (large effect). The Shapiro-Wilk test confirmed normal data distribution (p > 0.05). The findings indicate that group counseling using game-based techniques significantly improves academic resilience by enabling students to face challenges, adapt to rules, and collaborate in a supportive environment. In conclusion, game-based group counseling is an effective strategy for school counselors to enhance academic resilience among vocational students. Further research across different educational levels is recommended. Keywords: academic resilience, group counselling, game techniques, vocational high school